High temperature abrasion resistance of differently welded structural steels. (September 2017) - Rojacz, H.; Pahr, H.; Baumgartner, S.; Varga, M.
Abstract: Structural steels provide a broad spectrum of heat, creep and wear resistance at different microstructures and hardness levels. Two different steel grades were chosen for investigation and simulated repair welds with different parameters were performed, aiming on the influence of heat input during welding and the resulting microstructure on the high temperature abrasion resistance. The impact on the wear resistance and its temperature dependence was evaluated within a high temperature three-body abrasion test and a hot hardness test rig. Results indicate a strong dependence of present microstructural phases and hardness on the wear resistance entailed by different welding parameters. Optimised parameters and low energy input during welding leads to stable hot hardness progress and wear conditions for the investigated materials. Highlights: Repair/overlay welding can increase the wear resistance of the steel grades. Optimised welding leads to stable hot hardness and wear behaviour. Higher energy input and higher interpass temperature cause unstable wear behaviour. Suboptimal welding conditions lead to lowered hardness and higher wear rates. The importance of welding parameters on abrasive wear resistance was pointed out.